Accounting for the public good: Bridging profit and purpose in addressing Nigeria's development crisis - Opudu, Okubokeme Derek; Iweias, Seth Sokiri (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study investigates how public financial management indicators and corporate social responsibility (CSR) efforts influence national development in Nigeria. It focuses on understanding the link between fiscal governance, private sector accountability, and human development outcomes in the context of Nigeria’s persistent development crisis. Research Methodology: The research employs a quantitative ex-post facto design, analyzing secondary data from 2003 to 2022. Key variables include Capital Expenditure, Debt-to-Revenue Ratio, and the Corruption Perception Index, alongside CSR investment data. A structured econometric model using multiple regression analysis assesses their impact on the Human Development Index (HDI). Results: Findings reveal that capital expenditure has a significant positive impact on HDI, while corruption perception negatively affects development outcomes. Debt financing contributes positively when effectively managed. Conversely, CSR investments show statistically insignificant influence, indicating a disconnect between corporate initiatives and national development priorities. Conclusion: Effective public financial management, particularly in capital investment and anti-corruption strategies, remains crucial for enhancing Nigeria’s HDI. CSR’s limited developmental impact suggests the need for stronger integration into national planning. Limitations: The study is limited by data availability on CSR activities and potential measurement biases in perception-based corruption indices. The exclusion of qualitative CSR outcomes may also under-represent its long-term development impacts. Contribution: This study offers empirical evidence for aligning fiscal discipline with responsible corporate action. It contributes to stakeholder theory and public interest accounting by proposing policy frameworks that link profitability to purposeful national development, especially in emerging economies like Nigeria.